Advanced Engineering Materials for Enhancing Thermal Management and Thermal Safety of Lithium-Ion Batteries: A Review - Yang, Shichun; Lin, Jiayuan; Zhang, Zhengjie; Zhang, Cheng; Zheng, Xu; Xie, Wentao; Wang, Lijing; Chen, Siyan; Liu, Xinhua (Frontiers in Energy Research, 2022)
Lithium-ion batteries (LiBs) are the key power source for electric vehicles (EVs). Battery thermal management system (BTMS) is essential to ensure safety and extend service life of LIBs. This paper reviews the various refrigeration materials used in the BTMS in EVs, including liquid coolant, phase change material (PCM). The thermal properties of these refrigerant materials are summarized and the innovative ways to improve the cooling efficiency of the BTMS are analyzed. The various ways to enhance the battery’s thermal performance by modifying the materials of the electrode, separator, and electrolyte are also reviewed. Finally, the research prospect in area of BTMS is summarized. This review will inspire new BTMS design and further improvement in battery safety and performance with the aid of advanced intelligent technologies.